Study to Correlate Histopathological Spectrum of Gastrointestinal Malignant Neoplasm with Demographic Profile of The Patients - Panchal, Nital Vishnubhai; Panchal, Nirav Sureshbhai (Annals of Pathology and Laboratory Medicine, 2020)
Background: To study occurrence, age and sex distribution, to evaluate and to correlate the various histopathological features of surgical specimens of gastrointestinal tract tumours received at pathology department of GMERS medical college, Gandhinagar (Gujarat, India). Methods: A histopathological study of gastrointestinal tract tumours of 64 cases was carried out on surgical specimens at GMERS medical college, Gandhinagar from January-2018 to May-2019. Specimens were received in 10% formalin. After proper fixation and grossing of the specimens tissue processing was carried out. Blocks were made, sections were cut and stained with Harris Haematoxylin and Eosin stain and observed microscopically. Result: From the total of 64 cases: 42 Males and 22 Females were affected with peak occurrence in their sixth decade having anatomical distribution in oesophagus 07(10.93%), stomach 09(14.06%), small intestine 12(18.75%), appendix 01(01.56%), colon and rectum 34(53.12%) and anal canal 01(01.56%). Histological types diagnosed were- epithelial 53(82.81%), mesenchymal 06(09.30%), lymphoma 04(06.27%) and neuroendocrine tumor 01(01.56%). Conclusion: The occurrence of gastrointestinal tumours was highest in the colon and rectum accounting for 53.12% of cases with most common variety being epithelial. The peak age distribution was in the sixth decade. Male to female ratio was 1.9:1. As Gastrointestinal tumours show a wide variation in the morphology, histopathological examination is must for the diagnosis and typing of these tumours.